Membangun Keluarga Sakinah: Perspektif Hukum Keluarga Islam dan Peran Penyuluhan di Kabupaten Jember - Fawaid Fawaid; Fajar Ainol Yakin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
A sakinah family is understood as a harmonious family, where the values of Islamic teachings are upheld, and family members respect and love each other. In a sakinah family, each individual carries out their obligations well and helps each other. They also have a deep understanding of each other, so that conflicts that arise can be resolved in a good and wise way. This research discusses two main issues: the concept of a sakinah family in the perspective of Islamic Family Law and its implementation through the guidance of counselors in Jember Regency. The approach used is qualitative method, with data collection through observation, interview, and documentation. Data sources include primary and secondary data. The results showed that the concept of a sakinah family in Islamic Family Law is a family built on the basis of a legal marriage, hoping for the pleasure of Allah SWT, and prioritizing peace, tranquility, and happiness to achieve prosperity in the world and the hereafter. The sakinah family is the ideal condition expected by every individual in family life. Its implementation through counseling includes efforts to provide understanding to the community about the importance of building a sakinah family based on Islamic values. This counseling also targets prospective brides, including in the context of early marriage, so that they understand the meaning of marriage in accordance with the principles of sakinah, mawaddah, and rahmah.